Antioxidant therapy for patients with oral lichen planus: A systematic review and meta-analysis - Bao, Jie; Chen, Chu; Yan, Jiayu; Wen, Yueqiang; Bian, Jiamin; Xu, Mengting; Liang, Qin; He, Qingmei (Frontiers in Pharmacology, 2022)
Aims: This study aimed to systematically review the efficacy and safety of antioxidants for patients with Oral lichen planus (OLP). Methods: Databases, including PubMed, Web of Science, Cochrane Library, Embase, and Google Scholar, were searched up to April 30, 2022, for randomized controlled trials on the antioxidant therapy of OLP. The following endpoints were analyzed: pain score, clinical score, pain resolution rate, clinical resolution rate, and adverse effects. Results: A total of 19 studies met the inclusion criteria, and 17 studies with 704 patients were included in the meta-analysis. The findings showed that antioxidant therapy could significantly reduce the pain score [standardized mean difference –0.72 (–1.36, –0.07), P = 0.03, I2 = 87%, PI2 <0.00001] and clinical score [SMD –2.06 (–3.06, –1.06), P < 0.0001, I2 = 94%, PI2 < 0.00001] of patients with OLP and improve the pain resolution rate [risk ratio (RR) 1.15 (1.01, 1.31), P = 0.04, I2 = 45%, PI2 = 0.09) and clinical resolution rate [RR 1.40 (1.10, 1.78), P = 0.006, I2 = 72%, PI2 = 0.002]. Conclusion: The study demonstrated that antioxidant therapy was beneficial for patients with OLP, and antioxidants might be used to treat OLP.